T-20 and T-1249 HIV fusion inhibitors’ structure and conformation in solution: a molecular dynamics study - Martins do Canto, António Manuel Teixeira (2011)
Fusion of the HIV envelope with the target cell membrane is a critical step of the HIV entry into the target cell. Several peptides based on the C-region of HIV gp41 have been used in clinical trials as possible HIV fusion inhibitors. Among these are T-1249 and T-20 (also known as enfurvitide). Despite recent works, a detailed molecular picture of the inhibitory mechanism of these molecules is still lacking. These peptides are usually depicted as -helices by analogy with the structure of the sequence of the gp41 protein with which they are homologous. However, structures like these would be highly unstable in solution and thus would not explain, by themselves, the ability that the two fusion inhibitors have to become solvated by water and also interact effectively with cell membranes. To this effect, extensive molecular dynamics simulations were carried out to investigate the structure and conformational behavior of T-1249 and T-20 in water, as well as shorter homologous peptides CTP and 3f5, which show no inhibitory action. We found that the studied inhibitors have no stable structure in solution in the time scale studied. Additionally, the solvent accessible area varies significantly during the simulation. Our findings suggest that these peptides may assume not only one, but several possible sets of structures in solution, some of which more adequate to interact with the solvent, whereas others might be better suited to interact with cell membranes. Interestingly, and in accordance with published experimental studies, we verified that T-1249 displays considerably larger -helical structure than T-20. Taking into account a recent study with design peptides with increased helicity, it is possible that this feature may be related to the increased inhibiting efficiency of T-1249 relative to that of T-20.